Counseling on Making Simple Financial Statements to Bakery Businesses in Sampora Cibinong Village - Harza, Nanda Alwan (Jurnal Pengabdian Nusantara, 2024)
Real Work Lecture (KKN) is a form of community service activity by students with a cross-scientific and sectoral approach at certain times and regions. The implementation of KKN activities usually lasts between one to two months and takes place in village-level areas (REDSOBEK 2020). The word Counseling comes from the torch which means torch or tool to illuminate the dark situation. Based on the origin of the word, counseling can be interpreted as an activity to provide information or explanation to those who will be embroidered (Dosensosiologi.com 2020). Simple financial statements for MSMEs are reports consisting of statements of financial position, profit, and loss, and notes to financial statements. All three provide information to internal and external parties regarding the company's performance. The company as an entity must provide information to internal and external parties. Internal parties include management and employees, while external parties are owners, investors, creditors, customers, and the government. The provision of information is carried out because the company must communicate. The most relevant information used by companies in communicating is financial statements (UBICO and Consultant B 2020).